ANALISIS KENAKALAN DAN PERILAKU SISWA KELAS XI DI MA MIFTAHUL MIDAD KECAMATAN SUKODONO KABUPATEN LUMAJANG - Kurnia Ramadhan, Yashinta; Feren Fortu Nella Kinandi; Sarifah Nur Aini; Ani Qotuz Zuhro Fitriana (Conseils : Jurnal Bimbingan dan Konseling Islam, 2023)
Delinquency is a person's actions that are not in accordance with the rules and behavior is a certain regularity in terms of feelings, thoughts, and predispositions of one's actions towards the surrounding environment. The purpose of this study was to find out the forms of delinquency and behavior of class XI students at MA Miftahul Midad. This study also aims to find out whether the delinquency they commit will affect their behavior at school every day. The method used in this study is the Qualitative Research Method. Data collection was carried out by field studies through interviews, observations and documentation of counseling teachers and class Xl students at MA Miftahul Midad. The results of this study indicate that the form of delinquency committed by class Xl students of MA Miftahul Midad is classified as a type of mild delinquency and can still be overcome by the Counseling Guidance teacher. The behavior of students at MA Miftahul Midad is partly in accordance with the delinquency they commit and is influenced by the circle of friends at school. This means that the behavior of these students can be influenced by the misbehavior they do at school every day, even though their form of delinquency is still relatively mild and not done every day. The consequence of committing delinquency at school is an educational punishment that is in accordance with the rules at school.